Social studies in perspectives : economics - Mallari, Jan Phillip D. (Makati City : Diwa Learning Systems, 2006)
This book has been written based on the requirements of the Basic Education Curriculum (BEC) of the Department of Education (DEPED). This textbook is aimed at explaining different economic concepts, theories, and principles. It illustrates how economics can be used in one's daily life. Numerous examples and practical situations are also presented in this book to allow students to fully understand economics.
Includes bibliography
English text.
Keywords: economics